PENGEMBANGAN SUBMODUL APL-01, APL-02, DAN ASESMEN PADA SISTEM INFORMASI LEMBAGA SERTIFIKASI PROFESI BERBASIS WEBSITE DENGAN MENERAPKAN COLLABORATIVE CODING - Rahmadila Nurjannah; Ratih Indah Wardani; Rifqi Adiyatma; Didik Kurniawan; Tristiyanto Tristiyanto (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Lembaga Sertifikasi Profesi (LSP) is an institution that has met the requirements to carry out competency certification and obtain a license from Badan Nasional Sertifikasi Profesi (BNSP). the length of the certification process and the large number of participants registering cause a lot of piles of files, thus making the conventional certification process no longer effective because processing participant data takes a lot of time, as well as other possibilities that can hinder the certification process, such as files the certification is damaged or lost so that it can be detrimental to the registrant and LSP. The purpose of this research is to develop an LSP information system in the hope of assisting and facilitating LSP in carrying out the entire series of professional certification processes starting from the registration process until the completion and assessment of the competency test. This system was developed using the PHP programming language and the Laravel framework. The system development method in this research is the prototyping method. This system was developed in a team using a collaborative coding approach. Collaborative coding approach will certainly be easier to solve existing problems so that they get a solution faster. Testing on the development of this system uses the User Acceptance Testing (UAT) method by running a professional certification simulation and providing a questionnaire which will later be calculated using a Likert scale. The results of this research indicate that the LSP information system developed is able to support the professional certification process. Based on the results of system testing, it also shows that all the functionality of the LSP system that is made can run well and according to user needs.